Synthesis of Sodium Hydroxide from Traditional Salt through Electrolysis Process - Ariesta Artamevia, Nazwa; Khonsa Rezkania, Gita; Redjeki, Sri; Triana, Nurul Widji; Santi, Sintha Soraya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Indonesia is expected to compete with other countries in the industrial sector, which plays a crucial role in the economic growth of a nation for its development. In several industries in Indonesia, NaOH plays a critical role in the production process, serving both as a primary component and as a supporting component. In the chemical industry, the chlor-alkali process is a crucial electrolytic technique utilized. The products generated from this process include Cl2, H2, and NaOH. This research utilizes traditional salt as a raw material for the production of NaOH, considering that traditional salt has a high NaCl content and also contains H2O, which is expected to yield NaOH with optimal concentration. This study aims to produce technical-grade NaOH that complies with the Indonesian National Standard (SNI) by examining the effects of electrical voltage and electrolysis time on the NaOH produced through the electrolysis process. The stages of this research include the preparation of a salt solution, the electrolysis process, and product analysis. The study was conducted with an NaCl concentration of 86.72% at electrical voltages of 5, 7.5, 10, 12.5, and 15 volts during the electrolysis process. Additionally, the electrolysis durations used were 100, 150, 200, 250, and 300 minutes. The weight of NaOH produced at an electrical voltage of 12.5 volts and a time of 100 minutes was 1.081 grams of NaOH. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation, and Infrastructure SDG 12: Responsible Consumption and ProductionSDG 8: Decent Work and Economic Growth)SDG 13: Climate Action